The Usability of the Preliminary ICF Core Set for Hospitalized Patients After a Hematopoietic Stem Cell Transplantation From the Perspective of Nurses: A Feasibility Study - Stallinga, Hillegonda A.; Bakker, Janita; Haan, Sylvia J.; van Os-Medendorp, Harmieke; Kars, Marijke C.; Overgoor, Louis; Stewart, Roy E.; Roodbol, Petrie F. (Frontiers in Rehabilitation Sciences, 2021)
Background: A hematopoietic stem cell transplantation (HSCT) has major impact on patient’s functioning and perceived quality of life. To describe patient’s functioning, a preliminary set of 53 categories of the International Classification of Functioning, Disability and Health (ICF) as relevant for HSCT patients has been selected earlier by a Delphi study. For implementation of this preliminary ICF core set for patients after HSCT in clinical practice, a feasibility study was requested. Methods: A feasibility study was conducted in an explanatory mixed methods research design. Qualitative data was collected cross-sectional by semi-structured interviews based on specific topics related to feasibility regarding the use of the preliminary ICF core set for HSCT patients from the perspective of nurses (5 in ICF trained nurses and 5 regular, untrained, nurses). Quantitative data, exploring the use of the preliminary ICF core set in HSCT patients, was collected longitudinal by a mobile health application based on ICF in which the in ICF trained nurses registered patients’ functioning based on the ICF core set for HSCT patients. Results: Qualitative analysis indicated that using the preliminary ICF core set is practical and acceptable for providing information about HSCT patients’ functioning from the perspective of nurses. In addition, nurses indicated a demand for this information due to its impact on multidisciplinary meetings and clinical-decision making by involving relevant aspects of patients' functioning. Management support, trained staff, and designated time to focus on functioning are mentioned as requirements for successful implementation. Quantitative analysis demonstrated that the most used 30% (n=17) ICF categories are included in the preliminary ICF core set for HSCT patients (n=24). Energy (b130) was the most used ICF category. Family relationships (d760) was the most frequently and highly positive associated ICF category. Conclusions: From the perspective of nurses, the preliminary ICF core set for HSCT patients is feasible and relevant in gaining information regarding functioning. Applying this preliminary ICF core set for HSCT patients in the anamnesis and the nursing consultations contributes to this information. Further research is needed to look at the perspective of other professionals and HSCT patients themselves.